Imaging and spectrum of monolayer graphene oxide in external electric field. (November 2015) - Gao, Yan; Qin, Chengbing; Qiao, Zhixing; Wang, Baotian; Li, Weidong; Zhang, Guofeng; Chen, Ruiyun; Xiao, Liantuan; Jia, Suotang
Abstract: The recent boom in sensor and optical materials based on graphene oxide (GO) requires the improvement and control of its optoelectronic properties. Here, we report the imaging and spectrum of transmission and fluorescence for monolayer graphene oxide (mGO) in an external electric field. It is demonstrated that the image of mGO reveals pronounced spatial heterogeneity under an electric field, and the spectrum presents electrically reversible modulated features. We explain these phenomena by the electric-field-induced changes of electronic density of localized states (DOLS), and we perform the calculations for DOLS by using the first-principles density functional theory.